1961
DOI: 10.1139/b61-020
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation by Light of Sporulation in Trichoderma Lignorum (Tode) Harz

Abstract: Exposure of growing cultures to white light caused subsequent formation of a ring of coniclia-bearing mycelium a t the locatio~l occupied by their advancing ~nargins a t the tirne of irradiation. Violet and blue light were very effective in stimulating sporulation, green was less so, a~i d yellow and red mere ineffective. Ail exposure to xvhite light of the order of 1 foot-candle for 1 minute sufficcd to i~~i t i a t e the sporulation response. IManuscript received May 17, 1960. Coi~tribution from the Departme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1964
1964
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The culture of the Trichoderma viride RSR7 was maintained on potato dextrose agar (PDA) or corn meal agar (CMA) slants at 4 o C. For physiological studies M9 medium (Miller, 1972) with following composition was used: Na 2 HPO 4 , 6 g; KH 2 PO 4 , 3 g; NaCl, 0.5 g; NH 4 Cl, 1 g; distilled water 1000 ml. M9 salts and agar were autoclaved separately and then supplemented with 2 ml of 1 M MgSO 4 · 7H 2 O, 10 ml of 20% glucose, 0.1 ml of 1 M CaCl 2 and 0.5 ml of vitamin B 1 (thiamine hydrochloride).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The culture of the Trichoderma viride RSR7 was maintained on potato dextrose agar (PDA) or corn meal agar (CMA) slants at 4 o C. For physiological studies M9 medium (Miller, 1972) with following composition was used: Na 2 HPO 4 , 6 g; KH 2 PO 4 , 3 g; NaCl, 0.5 g; NH 4 Cl, 1 g; distilled water 1000 ml. M9 salts and agar were autoclaved separately and then supplemented with 2 ml of 1 M MgSO 4 · 7H 2 O, 10 ml of 20% glucose, 0.1 ml of 1 M CaCl 2 and 0.5 ml of vitamin B 1 (thiamine hydrochloride).…”
Section: Methodsmentioning
confidence: 99%
“…Danielson and Davey (1973a, b), Shukla and Mishra (1970), and Tye and Willet (1977) have studied nutritional aspects of Trichoderma, and Danielson and Davey (1973a, b), and Macauley and Griffin (1969) have studied their CO 2 and pH responses. It has been also reported that the sporulation varies with light and darkness (Miller and Reid, 1961). In spite of enormous research on Trichoderma spp.…”
mentioning
confidence: 99%
“…T. viride is one of the most prevalent species of various soil types and occurs in almost all latitudes. The adaptibility and simple nutrient requirements (WARCUP 1951;WARD and HENRY 1961;DANIELSON and DAVEY 1973), the rapid growth and abundant sporulation (BRIAN and HEMMING 1950;MILLER and REID 1961;AUBE and GAGNON 1969) and the antibiotic effects of its metabolites (SEIKETOV 1954;PERSSON-HIJPPEL 1963;WEBSTER and LOMAS 1964;IIACLE 1965;SLATER et al 1967;RICARD 1970), have encouraged numerous workers to study it, especially in artificial culture.…”
Section: Introductionmentioning
confidence: 99%